Investigating The Antifungal Activity of Atorvastatin Compared with Nystatin on Oral Candidiasis before and during Head and Neck Radiotherapy - Golestannejad, Zahra; Khozeimeh, Faezeh; Taheri , Sara; Feizi , Soha; Abbasi , Fatemeh; Saberi, Zahra; Faghihian, Elham; Dehghan , Parvin; Tadayon , Faezeh; Kheirkhah , Mahnaz; Nourmohammadi Najafabadi , Zeinab; Ataie, Zahra (Galen Medical Journal, 2024)
Background: Radiotherapy plays an imperative role in the control of head and neck malignancies; however, it can damage oral tissues and salivary glands. These damages can alter oral Candida species and lead to the expansion of oral candidiasis resistant to common antifungal mediators, including nystatin. Atorvastatin, a serum cholesterol-lowering drug, has potential antifungal activities by inhibiting the synthesis of ergosterol in the fungal wall and disrupting mitochondrial function. This study aimed to determine and equivalence the antifungal activities of nystatin and atorvastatin on Candida species isolated from the mouths of patients undergoing head and neck radiotherapy before and during radiotherapy. Materials and Methods: This was an in vitro laboratory research conducted on samples isolated from patients experiencing head and neck radiotherapy, before and during radiotherapy. After determining the Candida species using the PCR-RFLP method, the antifungal activity of both nystatin and atorvastatin was evaluated by microdilution method according to CLSI standards, and the minimum inhibitory concentration (MIC) and minimum lethal concentration (MFC) of each drug were measured. Results: According to our findings, atorvastatin had less activity in inhibiting and killing different Candida species compared to nystatin before and during radiotherapy. Before radiotherapy, the MIC and MFC indices for nystatin against Candida albicans (P <0.001), tropical (P<0.001) and glabrata (P<0.001) were significantly lower than these three indices (P-value <0.001) for atorvastatin. The results of these indices in the second week of radiotherapy were similar to the results before radiotherapy. The MIC and MFC results for Candida albicans and tropicalis were obtained with a P-value <0.001 and for glabrata with a P-value = 0.002. Conclusion: The discoveries of this study indicate that atorvastatin exhibits lower antifungal activity compared to nystatin in treating oral candidiasis among patients receiving head and neck radiotherapy, both before and during the treatment.